Review of the Brazilian harvestman genus Roeweria Mello-Leitão, 1923 (Opiliones: Gonyleptidae) - Bragagnolo, Cibele; Pinto-Da-Rocha, Ricardo (Zootaxa, 2009)
The genus Roeweria Mello-Leitão, 1923 is revised and a variation on external morphological characters and male genitalia is presented for Roeweria virescens (Mello-Leitão, 1923). The monotypic genus Harpachylus Roewer, 1943 is a junior synonym of Roeweria Mello-Leitão, 1923 because its type-species, H. tibialis Roewer, 1943 is a junior synonym of the type-species Roeweria bittencourti Mello-Leitão, 1923. Roeweria garrincha sp. n. from Cananéia, São Paulo, Brazil, is described and can be distinguished from other members of the genus by the presence of a ventral process on the penis and by very large ventral apophyses on the apex of the male femur and patella IV.